Characterization of the Campylobacter fetus sapA promoter: evidence that the sapA promoter is deleted in spontaneous mutant strains. - Tummuru, M K (1992)
Wild-type Campylobacter fetus cells possess S-layer proteins (S+ phenotype), whereas after laboratory passage, spontaneous stable mutants that do not express these proteins (S- phenotype) arise. To determine the molecular mechanisms by which C. fetus changes to the S- phenotype, we studied wild-type strain 23D, from which the sapA gene encoding the 97-kDa S-layer protein has been cloned, and strain 23B, a spontaneous S- mutant. We compared these strains with another pair of strains, LP (S+) and HP (S-). Southern analysis with the cloned sapA gene as a probe indicated that both pairs of strains have multiple sapA homologs. Using gene disruption and replacement techniques, we constructed an isogenic strain of 23D that differed only in sapA expression (strain 23D:401:1). A 6.0-kb HindIII fragment from 23D:401:1 containing 3.4 kb of sapA upstream region then was cloned into pBluescript to produce pBG101. Nucleotide sequence analysis of sapA upstream region revealed a consensus promoter at -121 bp from the translational start site. Primer extension analysis placed a single in vivo transcription initiation site at the -114-bp position of sapA. A DNA probe derived from the sapA promoter region hybridized to a 5.5-kb HindIII fragment of chromosomal DNA from strain 23D but not to DNA from strain 23B. Northern RNA blot analysis showed no sapA mRNA in strain 23B. These data indicate that the lack of S-layer protein expression in spontaneous mutant strains is caused by the deletion of promoter sequences.